Heavy-ion induced radiation effects in 50 nm NAND floating gate flash memories. (November 2019) - Yin, Ya-nan; Liu, Jie; Liu, Tian-qi; Ye, Bing; Ji, Qing-gang; Sun, You-mei; Zhou, Xin-jie
Abstract: Using the 86 Kr, 129 Xe and 209 Bi ions provided by the Heavy Ion Research Facility in Lanzhou (HIRFL), the short-term and long-term radiation effects induced by heavy ions induced in 50 nm NAND floating gate (FG) flash memories are investigated. The linear energy transfer (LET) value covers the range from 20.7 to 99.8 MeV·cm 2 /mg. Only upset errors in FG cells are observed due to that the flash memories are powered off and the peripheral circuitries are shielded during heavy ion irradiation. The errors in FG cells irradiated with ions of different LET values are decreasing with time under room temperature condition. After the reprogramming of flash memories, retention errors in FG cells are observed in some flash memories, which are irradiated by heavy ions with LET values greater than 37.6 MeV·cm 2 /mg. The dependence of single event upset, annealing of errors and retention errors in FG cells on the ion LET value is analysed and the underlying mechanisms are discussed. Highlights: Annealing of FG errors and retention errors in FG cells are observed after heavy ion irradiation. Different rates of annealing for diﬀerent ion LET are observed in 50 nm flash memories. The cross section of the retention errors is several orders of magnitude lower than that for the FG SEU.